Food Insecurity in Rural Households: A Case of the Southern Region of Lesotho - Mamakase Grace Sello; Mahalieo Flora Motanyane; Nthabiseng Anna Mokhesi; Relebohile Ntsieane (Current Perspectives in Agriculture and Food Science Vol. 9, 2024)
Background: The issue of food insecurity has emerged as an urgent concern and a top priority in developed and developing countries. Rural households are currently grappling with food insecurity and malnutrition due to various factors. These factors include droughts, floods, poor farming practices, the impact of the COVID-19 pandemic, high food prices, and the Russia-Ukraine war. Despite the global issue of food insecurity, there is a lack of information on the status of food insecurity at the household level in rural areas of Lesotho. Aim: This study sought to assess food insecurity and its determinants among rural households in the Southern region of Lesotho, specifically in the Quthing, Mohale’s Hoek, and Mafeteng districts. Methods: A community quantitative cross-sectional study was conducted, and interview schedules were administered to a sample of three hundred (n=300) rural households. Primary data for this study were obtained from rural households using a validated survey instrument. The study found a large proportion of rural households (95.3%, n=286) to be food insecure, as measured by the Household Food Insecurity Access Scale (HFIAS). Predictors of household food insecurity were determined using multiple regression analysis. The descriptive analysis method was used to describe data collected from sample households. Results: The regression analysis revealed that the number of children in a household (ß=.139,t=2.450, CI=.022, .198, p<0.05), marital status of the household head (ß=-.119,t=-2.110, CI=-.144, -.005, p<0.05), Land availability (ß=.252,t=3.079, CI=.123, .560, p<0.05), and Borrowing money from informal money lenders (ß=.153,t=2.227, CI=024, .389, p<0.05)were significant predictors of household food insecurity in the studied regions at p< 0.05 significance. The result indicated that 4.6% of the households in Mafeteng, Quthing, and Mohale’s Hoek were food secure, and 95.3% were food insecure. Conclusions and Recommendations: Given the high prevalence of food insecurity in rural households, the study suggests that understanding the determinants of food insecurity is essential to combating the issue. Local authorities should prioritize eradicating hunger by implementing practical and sustainable policies to effectively reduce household food insecurity.